2006
DOI: 10.1002/ccd.20643
|View full text |Cite
|
Sign up to set email alerts
|

Should we perform preoperative coronary angiography in all cases of atrial myxomas?

Abstract: The prevalence of coronary disease is high in patients with atrial myxomas yet routine angiography is not performed. Moreover, some tumors have angiographically detectable neovascularity, which can alter surgical planning. We report two cases that support our recommendation for performing coronary angiography in all cases diagnosed with cardiac myxomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…Nevertheless, some authors have suggested that coronary angiography should be performed routinely in patients with cardiac myxoma so as to detect the presence of a large supplying vessel [6]. Other authors have suggested that coronary angiography should only be performed in the case of selected patients, particularly those over the age of 40 years and those with atherosclerotic risk factors undergoing surgical removal of a cardiac mass [4].…”
Section: Discussionmentioning
confidence: 97%
“…Nevertheless, some authors have suggested that coronary angiography should be performed routinely in patients with cardiac myxoma so as to detect the presence of a large supplying vessel [6]. Other authors have suggested that coronary angiography should only be performed in the case of selected patients, particularly those over the age of 40 years and those with atherosclerotic risk factors undergoing surgical removal of a cardiac mass [4].…”
Section: Discussionmentioning
confidence: 97%
“…In the literature, coronary angiography in patients with cardiac myxomas was recommended to exclude concomitant coronary artery disease and to clarify the origin of tumor vascularity [6,7]. And in most case, neovascularization revealed by coronary angiography and even by echocardiography, CT, or MRI suggests cardiac malignancy.…”
Section: Discussionmentioning
confidence: 98%
“…There is little documented literature on the relationship between CAD and cardiac myxomas 8 . This article provides the first compilation of available angiographic data on adult patients with cardiac myxomas and CAD.…”
Section: Discussionmentioning
confidence: 99%
“…Actually, even patients without any risk factors can present with CAD 25 . Therefore, others suggest that all adult patients diagnosed with myxomas should undergo CA 5, 8, 18, 25, 26 . In fact, preoperative CA seems to be quite safe; thus far there has been no report of procedure-related complications 8, 16, 18, 2427 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation